Effect of Work Stress and Workload on Teacher’s Performance - Supriyanto, Nova; Lian, Bukman; Kesumawati, Nila (Graduate Program Magister Manajemen Pendidikan, 2022)
This study aims to determine the effect of work stress and workload on teacher’s performance at SMP Negeri Lempuing Jaya District during the Covid-19 pandemic. This research is a quantitative study conducted at SMP Negeri Lempuing Jaya District with 95 teachers as respondents. Data collection techniques in this study used observation, questionnaires, interviews, and documentation. Analysis prerequisite test using Normality Test, and Multicollinearity Test and Heteroscedasticity Test. As well as by using a simple regression technique t-test and multiple linear regression technique f-test. The results of this study can be summarized there is significant influence of work stress and workload variables partially and simultaneously on teacher’s performance.